GEOLOGICAL INTERPRETATION OF 2D SEISMIC REFLECTION PROFILES ONSHORE LEBANON: IMPLICATIONS FOR PETROLEUM EXPLORATION. (October 2016) - Nader, F. H.; Browning‐Stamp, P.; Lecomte, J.‐C.
Abstract : The first 2D seismic reflection acquisition onshore Lebanon was undertaken in 2013 by Spectrum Geo Ltd under the auspices of the Lebanese Ministry of Energy and Water. The surveys were recorded across a crustal‐scale restraining bend in the central part of the Levant Fracture System. This contribution presents a geological interpretation of processed 2D data from the 2013 campaign. Two east‐west trending seismic profiles were acquired and processed with a total linear distance of ∼80 km. Overall, a total of 16 key seismic reflectors were identified and mapped, and 20 faults were traced on the seismic profiles which were compared to geologic sections along the same acquisition path‐lines. This helped to age‐constrain the key reflectors and to assign the proper lithostratigraphic attributes to observed seismic packages. Interval velocities were determined every 500 m along each profile using the Dix equation to approximate the depth (in metres) for each time‐picked horizon (ms), and ultimately to correlate seismic packages and measured thicknesses with known and/or extrapolated geologic rock units. The 50 km long SLEB‐2D‐01‐13 profile (Batroun – Ainata, northern Lebanon) shows distinct seismic reflectors down to 2.5 seconds TWT. The deepest key reflector is believed to correspond to the middle Triassic evaporites which appear to have acted as a decoupling horizon. The interpreted profile displays the continuity of the overlying Qartaba structure, a potential viable exploration lead which merits further investigation. The 30 km long SLEB‐2D‐05‐13 profile (Aley – Barr Elias, central Lebanon) shows excellent seismic imaging below the Bekaa valley, reaching 4 seconds TWT. The deepest key reflector is associated with the base‐Jurassic horizon, 6300m to 8500m below ground level. Assumed Eocene platform carbonates underlie an interpreted Oligocene argillaceous package. These may form good hydrocarbon reservoir rocks if a viable petroleum system is present.